PENERAPAN TEORI POSTMODERNISME DALAM PRAKTIK PENGAWASAN HUKUM ADMINISTRASI NEGARA: STUDI KASUS LEMBAGA OMBUDSMAN - Firmansyah, Teguh; Haykal, Salman Daffa; Saputra, Errix Dwi; Tristan, Jose Immanuel (Universitas Stikubank, 2024)
The application of postmodernism theory in the practice of state administrative law supervision in the case study of the Ombudsman institution uses library research. This activity is related to library data collection methods. Postmodernism theory can help the Ombudsman understand that reality is not objective or measurable. The influence of postmodernism theory on the Ombudsman of the Republic of Indonesia can influence their approach in conducting oversight of the government. However, they must consider the challenges and find the right balance between an inclusive approach and objective standards to ensure fairness and truth in their oversight.